FAKTOR YANG MEMPENGARUHI ANTI OLIGOPOLI DAN PERSAINGAN BISNIS TIDAK SEHAT - Rizki Nurwijayanti; Icha Aprilia (Institut Agama Islam K.H. Sufyan Tsauri, 2024)
An unhealthy oligopoly will give rise to business competition for economists. For economists, the definition of Oligopoly is a form of imperfect market competition where the supply of products is controlled by a number of companies. Typically, the number of companies is more than two but less than ten. Every time a company changes its price, it will be considered by other companies because of mutual trust in the market. This research is literature research using a qualitative approach, namely by reviewing literature books in accordance with the theory discussed, especially regarding the scope of Oligopoly and unhealthy business competition. This qualitative method describes existing phenomena or realities, both natural and human engineered. The research results show that the phenomenon of oligopoly and unhealthy business competition is important to understand in the context of the development of the business world. Oligopoly, as a form of imperfect market, has several negative impacts on society, especially related to rising prices of basic necessities and a lack of flexibility to compete. However, oligopoly markets also have advantages, such as price stability which tends to be maintained, product innovation and efficiency in the processing process.